Enhancing anesthetic techniques for improving whisker stimulation response in the barrel cortex - Ye Yuan; Tian Liu; Jue Wang (PLoS ONE, 2025)
This study adopts and validates an anesthetic protocol designed for rat whisker stimulation experiments, achieving significant enhancements in the neural response of the barrel field cortex. By combining alpha-chloralose, low-dose Isoflurane (0.5%) and Dexdomitor, the protocol not only maintains a stable anesthetic state but also markedly improves the amplitude and latency of local field potential (LFP) signals. Experimental results reveal that LFP amplitudes in the barrel field under this protocol are twice as high as those achieved with Isoflurane and four times as high as those with Ketamine-Xylazine, with significantly shortened latencies and reduced noise interference. For the first time, power spectral analysis reveals a distinct enhancement of oscillatory power in the alpha (8–13 Hz) and beta (13–30 Hz) bands under alpha-chloralose anesthesia, diverging from the traditional dominance of delta (0.5–4 Hz) oscillations observed with other anesthetics. Mechanistically, this phenomenon may be attributed to alpha-chloralose’s unique modulation of GABAergic and glutamatergic pathways, promoting cortical desynchronization and enhanced sensory processing. This protocol offers new insights into optimizing sensory-evoked neural signal acquisition and provides a reference for future studies exploring neural modulation in sensory neuroscience.